Consent to minimally invasive tissue sampling procedures in children in Mozambique: A mixed-methods study - Khátia Munguambe (Public Library of Science (PLoS), 2021)
Background Minimally invasive tissue sampling (MITS), also named minimally invasive autopsy is a post-mortem method shown to be an acceptable proxy of the complete diagnostic autopsy. MITS improves the knowledge of causes of death (CoD) in resource-limited settings. Its implementation requires understanding the components of acceptability, including facilitators and barriers in real-case scenarios. Methods We undertook a mixed-methods analysis comparing anticipated (hypothetical scenario) and experienced (real-case scenario) acceptability of MITS among relatives of deceased children in Mozambique. Anticipated acceptability information was obtained from 15 interviews with relatives of deceased children. The interview focus was on whether and why they would allow the procedure on their dead child in a hypothetical scenario. Experienced acceptability data were obtained from outcomes of consent requested to relatives of 114 deceased children during MITS implementation, recorded through observations, clinical records abstraction and follow-up informal conversations with health care professionals and semi-structured interviews with relatives. Results Ninety-three percent of relatives indicated that they would hypothetically accept MITS on their deceased child. A key reason was knowing the CoD to take preventive actions; whereas the need to conform with the norm of immediate child burial, the secrecy of perinatal deaths, the decision-making complexity, the misalignment between MITS’ purpose and traditional values, lack of a credible reason to investigate CoD, and the impotency to resuscitate the deceased were identified as potential points of hesitancy for acceptance. The only refusing respondent linked MITS to a perception that sharing results would constitute a breach of confidentiality and the lack of value attached to CoD determination. Experienced acceptability revealed four different components: actual acceptance, health professionals’ hesitancy, relatives’ hesitancy and actual refusal, which resulted in 82% of approached relatives to agree with MITS and 79% of cases to undergo MITS. Barriers to acceptability included, among others, health professionals’ and facilities’ unpreparedness to perform MITS, the threat of not burying the child immediately, financial burden of delays, decision-making complexities and misalignment of MITS’ objectives with family values. Conclusions MITS showed high anticipated and experienced acceptability driven by the opportunity to prevent further deaths. Anticipated acceptability identified secrecy, confidentiality and complex decision-making processes as barriers, while experienced acceptability revealed family- and health facility-level logistics and practical aspects as barriers. Health-system and logistical impediments must also be considered before MITS implementation. Additionally, the multiple components of acceptability must be taken into account to make it more consistent and transferrable.